Pengaruh Anggaran Pendidikan, Jumlah Guru dan Jumlah Kelas terhadap Partisipasi Pendidikan Sekolah Menegah Pertama di Kabupaten/Kota Provinsi Sumatera Barat - Maharani Aulia R; Yulhendri Yulhendri (Jurnal Ecogen, 2020)
This study aims to determine and analyze: 1) The influence of the education budget on the gross enrollment rate of junior high school education, 2) The effect of the number of teachers on the gross enrollment rate of junior secondary school education, 3) the effect of the number of classes on the gross enrollment rate of school education junior secondary in regencies / cities in West Sumatra Province. This research is classified into descriptive and associative research. The data analysis technique used in this study in proving and testing the proposed hypothesis is a panel data regression model. The results of this study found that: 1) There is a negative and insignificant influence between the education budget on the gross enrollment rate of junior secondary education, 2) There is a negative and significant effect between the number of teachers on the gross enrollment rate of junior secondary education, 3) There is positive and significant effect between the number of classes on the junior high school education gross enrollment rate in the district / city of West Sumatra Province.Keywords: education budget, number of teachers, number of classes, rough participation rates